Thinking like a lawyer : essays on legal history and general history for John Crook on his eightieth birthday - Crook, J. A. (John Anthony); McKechnie, Paul, 1957- (Mnemosyne, bibliotheca classica Batava. Supplementum, 2002)
An exploration of the law and life of Rome. The contributors respond to John Crook's injunction to "think like lawyers" by ranging as far as Ancient Greece, Ancient Persia and modern Denmark to expound their themes and draw comparisons.